Redescription of the Mediterranean endemic parasitic isopod Anuropodione amphiandra (Codreanu, Codreanu & Pike, 1966) n. comb. (Crustacea: Isopoda: Bopyridae) from Munida rutllanti Zariquiey Alvarez, 1952, with new records from Turkey and a review of the genus Anuropodione Bourdon, 1967 - BOYKO, CHRISTOPHER B.; WILLIAMS, JASON D.; ÖKTENER, AHMET (Mediterranean Marine Science, 2018)
Seven species of bopyrid isopods were previously known from Turkish Mediterranean waters; a purported eighth species, Orthione griffenis Markham, 2004, is based on incorrect identification and likely represent Epipenaeon ingens ingens Nobili, 1906, a species already known from the area. In the present study, we report on specimens referable to Pleurocrypta amphiandra Codreanu, Codreanu & Pike, 1966, infesting Munida rutllanti Zariquiey Alvarez, 1952, collected from the southern Aegean Sea off Turkey; this species was formerly known only from the Mediterranean off Algeria and the Adriatic Sea. The species is redescribed and illustrated for the first time and transferred to Anuropodione Bourdon, 1967, which is reviewed and A. australiensis Bourdon, 1976, is transferred to Allorbimorphus Bourdon, 1976. A key to all species of Anuropodione and a list of all bopyrids found on squat lobsters and porcelain crabs in the Mediterranean are provided.